The construction of a quick TPACK evaluation tool and comparison of an integrative and transformational model - Ratnawati Susanto (Indonesian Counselor Association (IKI), 2021)
It is well recognized that the model of Technological Pedagogical Content Knowledge (TPACK) is one of the most prominent frameworks for describing teachers' skills to successfully educate students via the use of technology. Self-report questionnaires are often used in TPACK assessment, limiting the measures' validity, reliability, and practical application. The TPACK framework's underlying structure also causes confusion among participants. An integrated or transformational picture of how the TPACK knowledge domains interact was determined by the framework's inherent linkages. Methods and findings One hundred and seventeen pre-service elementary school teachers were issued a 42-item pilot questionnaire. Reliability analysis and confirmatory factor analysis were used to reduce the number of items on each subscale and to ensure that the model was well-fitting. Structural equation modeling was used to analyze the internal connections that existed between the components. In conclusion, the 28-item final TPAC questionnaire is a feasible and reliable tool for assessing pre-service teachers' knowledge, skills, and attitudes toward learning (TPACK). The intrinsic links between knowledge components in the TPACK paradigm also allow for a transformational interpretation to be applied.